PENGARUH QUICK RATIO (QR) DAN DEBT TO EQUITY RATIO (DER) TERHADAP DIVIDEN PAYOUT RATIO (DPR) PADA PT. SEMEN INDONESIA - Dhea Paramitha; M. Djauhari (Fakultas Ekonomi dan Bisnis, Universitas Jayabaya, 2025)
The Dividend Payout Ratio (DPR) is an important indicator that reflects a company's policy in distributing profits to shareholders, making it a primary concern for investors in assessing the level of return on investment. Because the DPR reflects the balance between the company's internal needs and the interests of shareholders, it is important to investigate the factors that influence it. Two factors worth examining are the Quick Ratio (QR) and the Debt to Equity Ratio (DER). This study uses a quantitative approach with multiple linear regression analysis methods. Before testing the hypothesis, descriptive analysis and classical assumption tests were conducted, which included tests for normality, multicollinearity, heteroscedasticity, and autocorrelation. Furthermore, a t-test (partial), F-test (simultaneous), and analysis of the coefficient of determination (Adjusted R²) were performed with a significance level of 5%. The results showed that QR and DER did not significantly influence the DPR, either partially (p-value 0.488 and 0.144) or simultaneously (p-value 0.329), with an Adjusted R² value of 0.028. This means that only 2.8% of the DPR variation can be explained by these two variables, while the remainder is influenced by other factors such as profitability and cash flow. Therefore, management is advised to consider other indicators in dividend policy, and investors should consider additional factors such as ROE and investment plans. Future research could add variables such as ROA, NPM, or FCF and use a time series or panel data approach for more comprehensive results.Keywords: Quick Ratio, Debt to Equity Ratio, Dividend Payout Ratio